Soil Seed Banks of Tree Species from Natural Forests, Restoration Sites, and Abandoned Areas in Chiang Mai, Thailand - Rungrojtrakool, Patsavipich; Tiansawat , Pimonrat; Jampeetong, Arunothai; Shannon , Dia Panitnard; Chairuangsri , Sutthathorn (Forestry Faculty, Universitas Hasanuddin, 2021)
Soil seed banks have been used for investigation of natural regeneration of forests. In this study, we compared seed density and species composition of soil seed banks of trees among natural forests, restored forests of different ages, and abandoned agricultural land. The soil seed banks were collected from a natural forest (NF), 12-year-old and 17-year-old restoration sites (RF12y and RF17y), and 17-year-old abandoned site (AA) at Ban Mae Sa Mai, Chiang Mai, Thailand. A seedling emergence technique was used to assess seed density and species of emerged seedlings was identified. We found 5-8 tree species at each site. Seed densities in the study areas ranged from 43 to 298 seeds/m2. The seed density of RF12y was significantly higher than that of both NF and AA but not significantly different than RF17y (p < 0.01). Although there was no significant relationship between the restoration ages and the seed densities of the soil seed banks, the species composition of standing vegetation was related to the seed bank species. Sorensen’s similarities between the species composition of the soil seed banks and the existing trees in each area were between 0 and 13.79%, suggesting seed dispersal of both within and across study sites. Eight out of fourteen species in the soil seed banks were dispersed into restoration sites without standing vegetation of those species. Seven of those were animal-dispersed species. The selected native trees, framework species, attracted small seed dispersers into the study areas, especially at the restoration sites. This finding suggests that active forest restoration improved natural regeneration in restoration sites as well as neighboring areas via seed dispersal.